ENDOGENOUS FERTILITY WITH A SIBSHIP SIZE EFFECT. (16th October 2015) - Brezis, Elise S.; Ferreira, Rodolphe Dos Santos
Abstract : Since the seminal work of Becker, the dynamics of endogenous fertility has been based on the trade-off faced by parents between the quantity and the quality of their children. However, in developing countries, where child labor is an indispensable source of household income, parents actually incur a negative cost by having an extra child, so that the trade-off disappears. The purpose of this paper is to restore the Beckerian quantity–quality trade-off when intergenerational transfers are upstream, in order to keep fertility endogenous. We do that by adding a negative "sibship size effect" on human capital formation to the standard Becker model. With a simple specification, we obtain multiplicity of steady states or, more fundamentally, the possibility of a jump from a state with high fertility and low income to a state with low fertility and high income, triggered by a continuous increase in the productivity of human capital formation.